Working Paper 11: A framework to assess governance of health systems in low-income countries (Basel Institute on Governance Working Papers, 2011)
As awareness of the role governance in the performance of health systems has increased, so has the need to come up with systematic means to evaluate governance shortcomings to develop adequate interventions.This working paper describes a framework to assess governance in the health systems of low-income countries that is intended to have empirical applicability with a problem-driven approach. The analysis is grounded on a re-categorization of governance dimensions for greater heuristic power, with an emphasis made on the importance of strategic systems design and accountability.The proposed methodology includes mapping of both formal and informal institutions, actors and networks. This underscores the idea that in order to properly address governance weaknesses it is of utmost importance to have an insight into whether the interplay of formal and informal norms facilitates or undermines system performance.
Keywords: corruption; health systems; public governance; service delivery